Community Environmental Education Through A Local Knowledge-Based Learning Program On Plastic Waste Management - Riana Sunari; Sri Nurhayati (Departement of Mathematics Education, 2023)
The background of the problem in this study is the problem of plastic waste which continues to grow with the increasing population and changes in people's lifestyles. The efforts made in dealing with plastic waste areone of them with activities that can provide environmental awareness education for the community, especially in West Bandung Regency. The purpose of this study is to describe a waste management learning program based on local wisdom in the context of environmental awareness education for the community in Tanimulya Village, West Bandung Regency. This researcher uses qualitative methods, a type of field research with an descriptive method. The data collection techniques used use observation, interview, and documentation techniques. The resource persons or informants in this study were 4 people. In data analysis, 3 stages are used, namely data reduction, data presentation stage, and verification / drawing conclusions. Based on the research, the following findings were obtained: 1) the plastic waste management learning program in Tanimulya Village was carried out first by identifying the learning needs of the community which placed the top priority on learning plastic waste management based on local wisdom, 2) learning plastic waste management based on local wisdom including material on waste sorting, making waste banks, and processing plastic waste become useful items, 3) the results of learning plastic waste management include reducing plastic waste in the community environment of Tanimulya Village, increasing community creativity and productivity in utilizing plastic waste, and increasing environmental awareness of the people of Tanimulya Village, West Bandung Regency